Multi-cellular 3D human primary liver cell culture elevates metabolic activity under fluidic flow. Issue 10 (21st May 2015) - Esch, Mandy B.; Prot, Jean-Matthieu; Wang, Ying I.; Miller, Paula; Llamas-Vidales, Jose Ricardo; Naughton, Brian A.; Applegate, Dawn R.; Shuler, Michael L.
<x xml:space="preserve">Abstract</x> We have developed a low-cost liver cell culture device that creates fluidic flow over a 3D primary liver cell culture that consists of multiple liver cell types, including hepatocytes and non-parenchymal cells (fibroblasts, stellate cells, and Kupffer cells).